Almost Periodic Dynamic of a Discrete Wazewska-Lasota Model - Hamaya, Yoshihiro (Communications in Mathematics and Applications, 2014)
The purpose of this article is to investigate the existence of an almost periodic solution of a discrete Wazewska-Lasota model involving a linear harvesting term\[x(n+1)-x(n)= -α(n)x(n+1) +_i=1^lβ_i(n)e^-γ_i(n)x(n-τ_i(n))-H(n)x(n-σ(n)),\] by using the contraction mapping principle, and we also show that the solution of above equation converge exponentially to an almost periodic solution by constructing a luxury Liapunov functional.